Do We Believe In Value? : Valuing Toll Road Sub Sector Companies Listed On Idx - Riko Hendrawan; Ariful Ulya (Jurnal Manajemen Indonesia, 2023)
The purpose of this to examining the intrinsic value of the shares of toll road operator companies in IDX in 2021. This research uses data from 2016 to 2020 to calculate the historical performance of each company and is projected from 2021 to 2025. We used pessimistic, moderate, and optimistic scenario. The method used is DCF method with FCFF approach and the calculation of the Relative Valuation method using PER and PBV approaches. The results based on the DCF-FCFF method showed that JSMR was overvalued for the pessimistic scenario and undervalued for the moderate and optimistic scenarios, while the calculation using the RV-PER method on JSMR showed that it was undervalued in the pessimistic and moderate scenarios and overvalued in the optimistic scenario. Also, based on the RV-PBV method, it showed undervalued in all scenarios. The DCF-FCFF results of CMNP issuers were undervalued in all scenarios, the RV-PER method was overvalued in all scenarios, and the RV-PBV were undervalued in all scenarios. Finally, META issuers were undervalued in the pessimistic scenario, and overvalued in the moderate and optimistic scenarios. RV-PER CMNP had undervalued results in the pessimistic scenario and overvalued in the moderate and optimistic scenarios, and the RV-PBV had undervalued results in the pessimistic scenario and overvalued in the moderate and optimistic scenarios. Keywords : DCF, FCFF, PBV, PER